Evaluation of the adverse reaction potential of three measels-mumps-rubella combination vaccines (2002)
Reports on efforts to compare the incidence of adverse events following the administration of three commercially available measels-mumps-rubella (MMR) combination vaccines.
Keywords: VACCINATION